ANTHROPOIDAL POUCH TECHNIQUE FOR HIGHLY RESORBED RIDGES - Kaira, Laxman Singh; Dabral, Esha (Journal of Health and Allied Sciences NU, 2013)
This article presents a case report on neutral zone technique used for treating a complete edentulous patient with resorbed ridges. It emphasizes on using materials available by the chairside to make impressions for resorbed ridges and to locate the neutral zone. It also presents certain modifications in technique for recording the neutral zone to achieving maximum prosthesis stability, comfort and function
Keywords: Resorbed Ridges; Neutral Zone; Admix